Training on Hospitality and Homestay Management in Lerep Tourism Village, Ungaran, Semarang Regency - Dima, Cindy Citya; Rahayu, Emik; Asshofi, Izza Ulumuddin Ahmad; Pranatha, Prima Setia Judha (Research and Social Study Institute, 2025)
Background: Lerep Tourism Village is a developed tourist village in Semarang Regency, focusing not only on the production of locally sourced goods but also as a center for education, recreation, and local wisdom. The lack of promotion of homestays in Lerep has prompted attention to introduce products and services through a hands-on learning concept in the village and to promote the village as a tourist destination with a unique tourism concept.Aims: The aim of this community service activity is to improve hospitality skills and homestay management in Lerep tourist village.Methods: This community service is carried out in July 2025 in Lerep Village, Ungaran, Semarang Regency through hospitality management training. 30 homestay owners joined, starting from preparation, focus group discussion, implementation, follow up phase, and content on service management literacy.Results: The results showed implementation of practice training with homestay owners are not only theory, but more practice is the best solution to engage with customers to develop hospitality skills. Practical training is urgently needed to improve the hospitality skills of homestay owners, with product and service innovation as the main priority to create uniqueness and enhance guest satisfaction. Additional support through technology implementation, mentoring and evaluation, sustainability programs, and innovations in marketing, management, and operational processes will strengthen the competitiveness of homestays in Lerep Tourism Village.